Noninvasive Diagnosis of Acute Rejection in Renal Transplant Patients Using Mass Spectrometric Analysis of Urine Samples: A Multicenter Diagnostic Phase III Trial - Gwinner, Wilfried; Karch, Annika; Braesen, Jan H.; Khalifa, Abedalrazag A.; Metzger, Jochen; Naesens, Maarten; Van Loon, Elisabet; Anglicheau, Dany; Marquet, Pierre; Budde, Klemens; Matz, Mareen; Arns, Wolfgang; et al. (Transplantation Direct, 2022)
Background. Timely recognition and treatment of acute kidney graft rejection is important to prevent premature graft failure. A predefined urinary marker set for acute T cell-mediated rejection (TCMR) containing 14 peptides was tested for this purpose in a multicenter in-place validation study. Methods. Three hundred twenty-nine prospectively collected and 306 archived urine samples from 11 transplant centers in Germany, France, and Belgium were examined. Samples were taken immediately before a biopsy, performed for graft dysfunction within the first transplant year. Primary outcomes were sensitivity and specificity of the marker set for the diagnosis of biopsy-proven acute TCMR, with prespecified thresholds of 83% for sensitivity and 70% for specificity. Results. Eighty-two patients (13%) had acute TCMR grade I-III. In relation to the biopsy diagnosis of TCMR, the sensitivity of the urine test was 0.66 (95% confidence interval, 0.56-0.76) and the specificity 0.47 (95% confidence interval, 0.43-0.51), with an area under the curve (AUC) of 0.60. The different TCMR grades I-III were not reflected by the marker set, and borderline TCMR was not specifically detected. Secondary independent masked assessment of biopsies consented by 2 pathologists revealed an interobserver kappa value of 0.49 for diagnosing TCMR, compared with the local center's diagnosis. Using this consensus diagnosis, the AUC of the urine test was 0.63 (sensitivity 0.73, specificity 0.45). Post hoc optimization of the marker set improved the diagnostic performance in the study cohort (AUC 0.67) and in an independent patient cohort (AUC 0.69). Conclusions. This study illustrates the difficulty of proteomics-based diagnosis of TCMR and highlights the need for rigorous independent in-place validation and optimization of diagnostic biomarkers.
CRIS-Team WoS Importer:2022-04-29